Sistem Pendidikan di Indonesia pada Masa ke Masa - Bakhrudin All Habsy; Alifia Puteri Nugroho; Syakira Zahira Shofa; Sherlyna Yuniar Nonitasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education is a fundamental aspect in the formation of human personality which continues to develop over time. In Indonesia, education has gone through a long history, with various efforts made to ensure that every citizen has equal and quality access to develop their potential optimally. This research aims to analyze and examine various theories and research results on the development of the Indonesian education system. The research uses qualitative methods with a literature review type. The results of this research include (1) a historical basis that studies past developments, (2) a philosophical basis that examines basic values, (3) a psychological basis that considers individual psychological aspects, (4) a sociological basis that examines social dynamics, (5) the Tut Wuri Handayani foundation which emphasizes support and encouragement from behind, (6) the science and technology foundation which utilizes developments in science and technology, and (7) the juridical foundation which adheres to the applicable legal framework.